Penerapan yoga brahmari pranayama dalam mengontrol resiko perilaku kekerasan pada pasien skizofrenia: Case report - Pratiwi, Amanda Septia; Dewi, Marita Kumala; Suyani, Sri (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2024)
Background: The risk of violent behavior is one of the problems of schizophrenia where individuals are at risk of harming themselves, other people and the environment. Patients with problems at risk of violent behavior who are treated in the Helikonia Room at RSJD Dr. RM. Soedjarwadi Klaten generally still experiences signs of symptoms such as unstable emotions, anger, tantrums, throwing things and speaking harshly. Therefore, pharmacological and non-pharmacological interventions are needed during hospital treatment, namely Brahmari Pranayama Yoga to control the risk of violent behavior in patients. Purpose: To determine the effectiveness of applying Brahmari Pranayama yoga in controlling the risk of violent behavior in schizophrenia patients. Method: This descriptive qualitative research uses a case study approach method on schizophrenia patients who experience problems with the risk of violent behavior by providing Brahmari Pranayama yoga therapy. This research was conducted in the Helikonia Room at RSJD Dr. RM. Soedjarwadi Klaten, Central Java Province. The measuring tool used in this research was an observation sheet of signs and symptoms of risk of violent behavior. Case study ethics uses informed consent, anonymity, and confidentiality. Results: RUFA score before the brahmari pranayama yoga intervention was carried out on Mrs. N is 15 (Intensive II) and after carrying out independent yoga intervention, listening to patient complaints, training to control anger verbally and spiritually, and administering medication according to the program. Conclusion: Providing brahmari pranayama yoga intervention carried out for 4 days was effective in reducing signs and symptoms in patients with a risk of violent behavior in patients. Suggestion: Future researchers can use the results of this intervention as basic data and reference in future research related to actions to control the risk of violent behavior with different interventions or other types of yoga.   Keywords: Risk of Violent Behavior; Yoga Brahmari Pranayama   Latar Belakang: Resiko perilaku kekerasan sebagai salah satu masalah skizofrenia dimana individu beresiko dapat mencelakai dirinya, orang lain, maupun lingkungan. Pasien dengan masalah resiko perilaku kekerasan yang dirawat di Ruang Helikonia RSJD Dr. RM. Soedjarwadi Klaten pada umumnya masih mengalami tanda gejala yang muncul seperti emosi yang belum stabil, marah-marah, mengamuk, membanting barang, dan bicara kasar. Oleh sebab itu, dibutuhkan intervensi farmakologis dan non farmakologis selama perawatan di Rumah Sakit yaitu dengan Yoga Brahmari Pranayama untuk mengontrol resiko perilaku kekerasan pada pasien. Tujuan: Untuk mengetahui efektivitas penerapan yoga brahmari pranayama dalam mengontrol resiko perilaku kekerasan pada pasien skizofrenia. Metode: Penelitian kualitatif deskriptif ini menggunakan metode pendekatan studi kasus pada pasien skizofrenia yang mengalami masalah resiko perilaku kekerasan dengan pemberian terapi yoga brahmari pranayama. Penelitian ini dilakukan di Ruang Helikonia RSJD Dr. RM. Soedjarwadi Klaten Provinsi Jawa Tengah. Alat ukur yang digunakan dalam penelitian ini berupa lembar observasi tanda dan gejala resiko perilaku kekerasan. Etika studi kasus menggunakan informed consent, anonymity, and confidentiality. Hasil: Skor RUFA sebelum dilakukan intervensi yoga brahmari pranayama pada Ny. N sebesar 15 (Intensif II) dan setelah dilakukan intervensi yoga secara mandiri, mendengarkan keluhan pasien, melatih mengendalikan marah dengan verbal dan spiritual, dan memberikan obat sesuai program. Simpulan: Pemberian intervensi yoga brahmari pranayama yang dilakukan selama 4 hari efektif menurunkan tanda dan gejala pada pasien dengan resiko perilaku kekerasan pasien. Saran: Peneliti selanjutnya dapat menggunakan hasil intervensi ini sebagai data dasar dan acuan dalam penelitian selanjutnya yang berkaitan dengan tindakan untuk mengontrol resiko perilaku kekerasan dengan intervensi yang berbeda atau jenis yoga yang lain.   Kata Kunci: Resiko Perilaku Kekerasan; Yoga Brahmari Pranayama.